1989
DOI: 10.1128/iai.57.8.2470-2474.1989
|View full text |Cite
|
Sign up to set email alerts
|

A major antigen on the outer envelope of a human oral spirochete, Treponema denticola

Abstract: Human oral spirochetes are prominent inhabitants of subgingival plaque in patients with periodontal disease. By immunoelectron microscopy using protein A-gold complexes and either polyclonal mouse antiserum against the 53-kDa antigen or 53-kDa-antigen-specific monoclonal antibody, a major polypeptide antigen, with a molecular weight of 53,000 (molecular size, 53 kilodaltons [kDa]), of a human oral spirochete, Treponema denticola ATCC 33520, was found to localize on the surface of the outer envelope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 17 publications
2
31
1
Order By: Relevance
“…We previously reported that a major surface protein with a molecular size of 53,000 daltons (53 kDa) is located on the outer surface of an outer envelope of Treponema denticola ATCC 33520 (13 , 14). The 53-kDa surface protein of the ATCC 33520 seems to be immunologically different from that of the ATCC 35404 which Haapasalo et al reported (4), because the antiserum against the 53-kDa protein from the ATCC 33520 showed no cross-reactivity with that of the ATCC 35404 (14). T. UMEMOTO ET AL tion would be obtained.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…We previously reported that a major surface protein with a molecular size of 53,000 daltons (53 kDa) is located on the outer surface of an outer envelope of Treponema denticola ATCC 33520 (13 , 14). The 53-kDa surface protein of the ATCC 33520 seems to be immunologically different from that of the ATCC 35404 which Haapasalo et al reported (4), because the antiserum against the 53-kDa protein from the ATCC 33520 showed no cross-reactivity with that of the ATCC 35404 (14). T. UMEMOTO ET AL tion would be obtained.…”
mentioning
confidence: 91%
“…1 , lane 1). The 53-kDa protein of the ATCC 33520 is a predominant surface antigen on the outer envelope (14). The 45 , 000-P fraction was predominantly composed of axial flagella and membrane vesicles as a minor cellular component, when observed by electron microscopy (13).…”
mentioning
confidence: 98%
“…Such a limited surface exposure of Msp is in agreement with previous reports on the di¡erences in antigenicity of Msp between the ATCC strains of T. denticola. Umemoto et al [16] suggested a di¡erence in antigenicity between T. denticola ATCC 33520 and ATCC 35405; however, the amino acid sequences of these strains showed 91% identity. Fenno et al [17] reported that only residues between 204 and 271 of the 547 amino acids of T. denticola ATCC 35405 di¡er from those of T. denticola ATCC 33520, and suggested that these might lie in the surface-exposed region.…”
Section: Major Outer Sheath Proteinmentioning
confidence: 99%
“…Detailed information about the quantity, quality and behaviors or bacterial antigens of these organisms may lead to understanding their role in control of human periodontal diseases. We reported that a strain-specific 53,000-(53-kDa) antigen of T denticola American Type Culture Collection (ATCC) strain is located on the surface of the outer envelopes and that this major polypeptide might share with hexagonally arranged polygonal structure each possessing three pores in the outer envelopes (18,19). Some antigenic proteins were also found in human oral spirochetes and were utilized as probes or indicators to examine their associations with periodontal diseases (9,13,14,21).…”
Section: Strainsmentioning
confidence: 99%
“…After staining the polypeptides of each strain with Coomassie brilliant blue dye, two polypeptides, one with a molecular size of 34 kDa from a human oral isolate strain G7201 and the other with a molecular size of 38 kDa from T. denticola ATCC 35404, were selected on the basis of individual quantity, clear separation from neighboring protein bands and exclusion of the protein bands with the apparently similar molecular sizes. Polyacrylamide gel strips containing the 34-kDa polypeptide band from the strain G7201 or the 38-kDa polypeptide band from T. denticola ATCC 35404 were individually pooled, and each immunogen for production of polyclonal antiserum was prepared as previously reported (18). Female white rabbits were immunized with each immunogen with a total amount of approximately 180 ,ug of protein in four weeks.…”
Section: Strainsmentioning
confidence: 99%